(untitled) (LEARNing Landscapes, 2024)
This inquiry investigates the effects of trauma on students by analyzing personal experiences and teaching methods. Through the lens of autoethnography, a nonfictional storytelling approach, I reflect on my learning journey to identify compassionate and mindful teaching practices, aiming to foster a trauma‑sensitive classroom environment. Emphasizing the significance of teachers sharing their stories through autoethnography, this exploration contributes valuable insights to the ongoing discourse on trauma-informed pedagogy for student wellbeing.